Evaluation of a Mixed CAD Gear Modeling from Time and Precision Point of View. (2015) - Tolvaly-Roşca, Ferenc; Forgó, Zoltán; Máté, Márton
Abstract: The aim of the paper is to present an evaluation of a new mixed CAD modeling method, capable to universally build surfaces and solid models of gears. The proposed CAD solution builds gear models, primary not for a visual simulation of the gearing processes, but for complex gearing- and FEA studies in virtual environment. Localization of the contact paths of gear pairs, virtual kinematic evaluations, rapid verification of newly developed gear types and FEA analysis requires satisfactorily precise surface and solid models. The known NURBS modeling methods are mainly based on the analytical equations of the flanks of the teeth surfaces. The bottom and tip surfaces of the teeth, are very important in meshing and FEA studies, and generally cannot be built from the meshing equations. As the new mixed modeling method proposes a simplified and quick CAD modeling procedure, with flexible modeling options like rapid tool profile modifications, an evaluation of the obtained models must be made, from both: generating time and precision point of view. For this purpose, a model of a spur cylindrical gear (generated by a convolute helical hob) is built using the Solid Boolean Subtraction method and is compared with the gear generating process using a new mixed CAD method.